Usability Engineering: Interdisziplinäre Beiträge für eine verständlichere Rechtssprache - Lutz, Benedikt (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
In computer science, a new sub-discipline has been established in the last 3 decades that deals with the usability of user interfaces: Usability engineering offers a range of methods and tools to clarify essential requirements, make it easier for users to interact with interfaces, prevent incorrect input and make access to content more attractive in terms of improved "user experience".Many of these methods can also be applied to the creation of complex technical texts, and technical writers have already had good experience with them. These experiences can – mutatis mutandis -- also be helpful for the creation and optimisation of legal texts, from the planning process for new laws to optimising the design of mass notifications in administrative law. This article presents some of these principles and methods, each with examples of their application to different types of legal and administrative texts.
Keywords: comprehensible legal language; usability engineering; practical methods; interdisciplinarity